Kinetics of Ag-rich precipitates formation in Cu-Al-Ag alloys - Adorno, A. T.; Guerreiro, M. R.; Silva, RAG (Elsevier B.V., 2004)
The kinetics of Ag-rich precipitates formation in the Cu-2 wt.% Al alloy with additions of 2, 4, 6, 8, 10 and 12 wt.% Ag was studied using microhardness changes with temperature and time, differential scanning calorimetry (DSC), differential thermal analysis (DTA), scanning electron microscopy (SEM), optical microscopy (OM), energy dispersive X-ray analysis (EDX) and X-ray diffractometry (XRD). The results indicated that an increase in the Ag content decreases the activation energy for Ag-rich precipitates formation, and that it is possible to estimate the values of the diffusion and nucleation activation energies for the Ag precipitates. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: microhardness; kinetics; diffusion; nucleation; Cu-Al-Ag alloys